2014
DOI: 10.4184/asj.2014.8.2.150
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Findings and Results of Surgical Resection of Thoracolumbar Osteoid Osteoma

Abstract: Study DesignDescriptive, cases series study.PurposeTo evaluate clinical findings and results of treatment of patients with spinal osteoid osteoma who underwent surgery.Overview of LiteratureOsteoid osteoma is a benign tumor with spinal involvement rate of about 10%. It is manifested during adolescence with symptoms such as painful scoliosis. To treat the problem, operation on the patients and excising the nidus are suggested.MethodsThis descriptive study was conducted on 11 patients with spinal osteoid osteoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 16 publications
1
21
0
Order By: Relevance
“…Scoliosis resulting from spinal OO was observed to be more pronounced in lumbar vertebra involvement and was more severe in youths than in adults (6). Also, when the fourth or fifth lumbar vertebra is involved, it was generally associated with pelvic obliquity (17).…”
Section: Scoliosismentioning
confidence: 95%
See 1 more Smart Citation
“…Scoliosis resulting from spinal OO was observed to be more pronounced in lumbar vertebra involvement and was more severe in youths than in adults (6). Also, when the fourth or fifth lumbar vertebra is involved, it was generally associated with pelvic obliquity (17).…”
Section: Scoliosismentioning
confidence: 95%
“…In a study from pathology laboratory of a big university hospital, only 8 out of 131 OOs were located in the spine or sacrum (6.1%) (5). Therefore, spinal OO series are usually small and largest series in literature consist of 5 to 81 cases (4)(5)(6)(7)(8)(9)(10) Osteoid osteoma usually occurs in the first 3 decades of life and 90% of the patients are younger than 25 years. However, there are a few older patients in literature (12).…”
Section: Incidence Location and Demographic Characteristicsmentioning
confidence: 99%
“…[4,7] However, for cases at the early stage of osteoid osteoma, they may not present with obvious pain. [8] The incidence of osteoid osteoma-related scoliosis varies from 20% to 70%, [911] and spinal scoliosis is mainly due to chronic muscle cramps and inflammatory reactions surrounding the tumor. [12] X-ray examination has its limitation in diagnosing osteoid osteoma as the tumor nest often locate at concave side of the apical segment; by contrast, radionuclide bone scanning has its advantage in locating the lesion.…”
Section: Discussionmentioning
confidence: 99%
“…[14,15] The misdiagnosis rate is reported to be as high as 54.5%. [9] Uehara et al [1] reported a case of misdiagnosis of osteoid osteoma at the lamina of the 10th thoracic vertebra, which they presumed to be scoliosis and planned to perform posterior correction surgery, but as the preoperative CT examination revealed manifestations of osteoid osteoma, they corrected the diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Most spinal OO are located in the posterior elements of the vertebra. Stiff and painful scoliosis is the most typical presentation (20–70% of cases) [3]. Muscular spasm may result in scoliosis, which is initially non-rotational.…”
Section: Osteoid Osteomamentioning
confidence: 99%